Faktor-faktor yang mempengaruhi produksi kopi arabika - Hugolinus J. B. Pangkur; Marthen R. Pellokila; I Nyoman Sirma (Journal of Agricultural Socio-Economics (JASE), 2020)
Coffee has become the foundation of the economy of the community, including in Manggarai, East Nusa Tenggara. In running their farms, farmers find a problem, namely low production. The purpose of this study was to analyze the relationship and influence of Arabica coffee production factors. The sample in this study amounted to 83 farmers. The research data uses primary and secondary data. The data analysis method uses correlation analysis (Bivariate Correlation) and the Cobb Douglas production function model. The results showed that the factors that have a relationship with Arabica coffee farming production are fertilizer, seeds, labor, land area, and household size. In contrast, factors that have no relationship with production are education level, farming experience, and farmer's age. The factors that affect the production of Arabica coffee farming are seeds, land area, and household size. In contrast, factors that did not affect production were fertilizer, education level, labor, farming experience, and age